Swabian MOSES 2021: An interdisciplinary field campaign for investigating convective storms and their event chains - Kunz, Michael; Abbas, Syed S.; Bauckholt, Matteo; Böhmländer, Alexander; Feuerle, Thomas; Gasch, Philipp; Glaser, Clarissa; Groß, Jochen; Hajnsek, Irena; Handwerker, Jan; Hase, Frank; Khordakova, Dina; et al. (Frontiers in Earth Science, 2022)
The Neckar Valley and the Swabian Jura in southwest Germany comprise a hotspot for severe convective storms, causing tens of millions of euros in damage each year. Possible reasons for the high frequency of thunderstorms and the associated event chain across compartments were investigated in detail during the hydro-meteorological field campaign Swabian MOSES carried out between May and September 2021. Researchers from various disciplines established more than 25 temporary ground-based stations equipped with state-of-the-art in situ and remote sensing observation systems, such as lidars, dual-polarization X- and C-band Doppler weather radars, radiosondes including stratospheric balloons, an aerosol cloud chamber, masts to measure vertical fluxes, autosamplers for water probes in rivers, and networks of disdrometers, soil moisture, and hail sensors. These fixed-site observations were supplemented by mobile observation systems, such as a research aircraft with scanning Doppler lidar, a cosmic ray neutron sensing rover, and a storm chasing team launching swarmsondes in the vicinity of hailstorms. Seven Intensive Observation Periods (IOPs) were conducted on a total of 21 operating days. An exceptionally high number of convective events, including both unorganized and organized thunderstorms such as multicells or supercells, occurred during the study period. This paper gives an overview of the Swabian MOSES field campaign, briefly describes the observation strategy, and presents observational highlights for two IOPs.